Contenido y alcance jurisprudencial del bloque de constitucionalidad en Colombia (2007)
The Constitutional Body of Law (Bloque de Constitucionalidad) is one of the most important contributions of the Constitution of 1991 to the Colombian legal system. Its key role is to serve as a receptive instrument of international law, ensuring consistency of domestic legislation with the commitments ad extra of the State, and at the same time, serve as a complement to guarantee human rights and IHL in the country. However, since the jurisprudence of the Constitutional Court is solely responsible for its regulation, and very few efforts exist today to develop from it the corresponding rules and subrules, ignorance on the value, content and scope of the Body of Law, results in a risk to the country’s legal security andpossibly, the citizens’ lack of knowledge about their rights.This article, the product of a long and methodical investigation, explains the result of the identificationof the constitutional jurisprudence lines in the area of the Constitutional Body of Law, essentially determining the legal status and content of this instrument, in order to establish value, as a formalsource, of some treaties and some of their interpretations, in domestic law.